2023
DOI: 10.3389/fendo.2023.1190547
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves intestinal IgA production by T-dependent cell pathway in adults but not in aged mice

Angel Joel Hernández-Urbán,
Maria Elisa Drago-Serrano,
Andrea Cruz-Baquero
et al.

Abstract: IntroductionHypermutated high-affinity immunoglobulin A (IgA), neutralizes toxins and drives the diversification of bacteria communities to maintain intestinal homeostasis although the mechanism underlies the impact of moderate aerobic exercise (MAE) on the IgA-generation via T-dependent (TD) is not fully know. Therefore, the aim of this study was to determine the effect of long-time MAE on the production of IgA through the TD pathway in Peyer´s patches of the small intestine from aged mice.MethodsMAE protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…These findings suggested that MAE improved the intestinal response by enhancing the APRIL mRNA level associated with the T-cell independent pathway of B cell response committed for an increase of IgA generation. Findings support the impact of MAE on the increase (twofold) of intestinal IgA concentration in aged mice by comparison with senile sedentary mice [33].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…These findings suggested that MAE improved the intestinal response by enhancing the APRIL mRNA level associated with the T-cell independent pathway of B cell response committed for an increase of IgA generation. Findings support the impact of MAE on the increase (twofold) of intestinal IgA concentration in aged mice by comparison with senile sedentary mice [33].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, the loss of Pax5 levels during terminal differentiation contributes to the plasma cell transcription program to IgA CSR [9]. In spite of the plasma cell number was unchanged by the exercise, in this study increased luminal IgA concentration (previously reported [33] ), and α-chain mRNA level found in exercised mice may result from the decrease of Pax5 mRNA favoring both the IgA plasma cell surviving and IgA CSR.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations